To the history of the Oirat Buddhist monastery Ablai-kit - N. V. Tsyrempilov (Nomadic Civilization: Historical Research, 2021)
In this article, the subject of consideration is the ruins of the Ablai-Kit monastery in Dzungaria, discovered by an expedition led by the guard, Major Ivan Mikhailovich Likharev. Ablai Kit is of great interest to archaeologists who study it as a historical monument. The monastery contained a library that was signiﬁcant for the periphery of the Tibeto-Buddhist world at that time. The various ﬁnds found in the monastery, especially manuscripts, are of particular value to the world scientiﬁc community. The text of one of the sheets of the manuscript became the subject of painstaking analysis by specialists and discussion among Tibetan scholars. The extant text of the leaf, as well as other manuscripts found in the ruins of the monastery, are a valuable source for historians studying the political and cultural history of the Oirat state and Buddhist monasteries on the territory of modern Kazakhstan.